2018
DOI: 10.1136/archdischild-2018-315909
|View full text |Cite
|
Sign up to set email alerts
|

County lines: how gang crime is affecting our young people

Abstract: ‘County lines’ is the term used for the proliferating mobile phone lines used by gangs to infiltrate county towns where a profitable drug market is identified. The National Crime Agency reports that 88% of police areas in England and Wales have either an established or emerging County Lines problem in their area. With an estimated 46 053 aged 10–18 years in England in a gang, the activities of gangs and County Lines have a devastating impact on young people, vulnerable adults and local communities. Young peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…In this study, we report a unique geographical distribution of penetrating torso trauma cases attended by HEMS, largely aligning to the drug-trafficking county lines [ 21 , 22 ]. The multi-agency Kent and Medway Gang Strategy (2018–2021) warn of steadily increasing gang operations across the Kent and Medway region, originating from London-based individuals venturing into the region for ‘homegrown’ gangs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we report a unique geographical distribution of penetrating torso trauma cases attended by HEMS, largely aligning to the drug-trafficking county lines [ 21 , 22 ]. The multi-agency Kent and Medway Gang Strategy (2018–2021) warn of steadily increasing gang operations across the Kent and Medway region, originating from London-based individuals venturing into the region for ‘homegrown’ gangs.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of early 'journey-to-crime' studies suggested that travel associated with crime is limited and mostly local in nature (e.g. Wiles and Costello 2000). However, emergent international studies have increasingly found offender travel to be more widespread with long crime trips more common than first reported (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Berridge et al, 2001) and lead to increased risk of victimisation (McAra & McVie, 2010). Given widespread concerns about the vulnerability of young people in relation to gang-related activity and involvement in 'county lines' (Glover Williams & Finlay, 2018;Stone, 2018;National Crime Agency, 2019), the benefits of a holistic, 'one service approach' seem more important than ever.…”
Section: Discussionmentioning
confidence: 99%